2002
DOI: 10.1603/0022-0493-95.4.754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kaolin-Based Particle Film Application on Boll Weevil (Coleoptera: Curculionidae) Injury to Cotton

Abstract: This study examined a non-insecticidal tactic for suppressing boll weevil, Anthonomus grandis grandis Boheman, damage to cotton, Gossypium hirsutum L. In cage assays, kaolin, a reflective white mineral, applied to excised cotton squares or to the cotton foliage, initially resulted in lower levels of boll weevil injury to squares than nontreated squares. Boll weevil oviposition and feeding on kaolin-treated squares and squares on kaolin-treated cotton plants increased when nontreated squares and cotton plants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
1
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 23 publications
2
57
1
14
Order By: Relevance
“…In general, those and other studies showed kaolin as an effective substance in reducing the population of several groups of pests, such as Hemiptera (Daniel et al, 2005;Alavo and Abagli, 2011;Martinou et al, 2014), Lepidoptera (Showler, 2003;Sackett et al, 2007), Diptera (Mazor and Erez, 2004;Pascual et al, 2010) and Coleoptera (Silva and Ramalho, 2012). Kaolin acts as a repellent or barrier for pests, affecting the recognition and attractiveness of host plants (Showler, 2002).…”
Section: Introductionmentioning
confidence: 76%
“…In general, those and other studies showed kaolin as an effective substance in reducing the population of several groups of pests, such as Hemiptera (Daniel et al, 2005;Alavo and Abagli, 2011;Martinou et al, 2014), Lepidoptera (Showler, 2003;Sackett et al, 2007), Diptera (Mazor and Erez, 2004;Pascual et al, 2010) and Coleoptera (Silva and Ramalho, 2012). Kaolin acts as a repellent or barrier for pests, affecting the recognition and attractiveness of host plants (Showler, 2002).…”
Section: Introductionmentioning
confidence: 76%
“…Assim, a pulverização da lavoura com o caulim vem sendo testada visando à redução das infestações da lavoura pelo bicudo (SHOWLER, 2002;RAMALHO, 2013). O caulim é um produto deterrente que pode repelir diretamente ou tornar as plantas hospedeiras irreconhecíveis ou impróprias para sítios de alimentação e oviposição (GARCIA; BERKETT;BRADSHAW, 2003).…”
unclassified
“…O caulim é um produto deterrente que pode repelir diretamente ou tornar as plantas hospedeiras irreconhecíveis ou impróprias para sítios de alimentação e oviposição (GARCIA; BERKETT;BRADSHAW, 2003). A atratividade do bicudo pela folhagem das plantas cobertas por caulim é reduzida em relação às plantas sem essa cobertura, em chance de escolha (SHOWLER, 2002). Esse efeito pode ser explorado como alternativa para reduzir a colonização da lavoura, inclusive em associação com outras técnicas de manejo, como a possibilidade do uso do caulim pulverizado no interior da lavoura associado à pulverização de inseticida convencional nas bordaduras (SILVA; RAMALHO, 2013).…”
unclassified
See 2 more Smart Citations